2012
DOI: 10.3724/sp.j.1227.2012.00241
|View full text |Cite
|
Sign up to set email alerts
|

The impact of land use change on soil organic carbon and labile organic carbon stocks in the Longzhong re-gion of Loess Plateau

Abstract: Land use change (LUC) is widely recognized as one of the most important driving forces of global carbon cycles. The soil organic carbon (SOC) and labile organic carbon (LOC) stores were investigated at arable land (AL), artificial grassland (AG), artificial woodland (AW), abandoned arable land (AAL) and desert steppe (DS) in the Longzhong region of the Loess Plateau in Northwest China. The results showed that conversions from DS to AL, AL to AG and AL to AAL led to an increase in SOC content, while the convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 20 publications
4
27
0
Order By: Relevance
“…Similarly, Li et al (2004) reported that conversion of natural forests to continuous cultivation and grazing decreased both the concentration and stock of SOC. Zhang et al (2012) found that SOC stock increased when arable cropland was abandoned. In our case, the lowest SOC stock was found under abandonment (RdA2).…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%
“…Similarly, Li et al (2004) reported that conversion of natural forests to continuous cultivation and grazing decreased both the concentration and stock of SOC. Zhang et al (2012) found that SOC stock increased when arable cropland was abandoned. In our case, the lowest SOC stock was found under abandonment (RdA2).…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%
“…Emissions from land use and land cover change are believed to be the second most significant source of human‐induced greenhouse gas emissions into the atmosphere (1.6 Pg C/a) after fossil fuel combustion (7.2 Pg C/a) (IPCC (Intergovernmental Panel on Climate Change) , Zhang et al. , Wang et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, 0.1-0.5 g air dried soil samples passed through a 0.15 mm sieve were digested in 5 mL of 0.8 mol¨L´1 K 2 Cr 2 O 7 and 5 mL concentrated H 2 SO 4 (1.84 g¨mL´1) for 5 min at 170-180˝C. Secondly, the digested solution samples were titrated with standardized 0.2 mol¨L´1 FeSO 4 solution mixed with 15 mL concentrated H 2 SO 4 per litre to prevent oxidization [32,33]. After the analysis, the soil organic C stock (Mg¨ha´1) for each layer was calculated using the following formula [34]:…”
Section: Soil Sampling and Analysismentioning
confidence: 99%